'Deeply odd': women veterans as critical feminist scholars. Issue 1 (2nd January 2023) - West, Hannah; Antrobus, Sophy
ABSTRACT: A series of conversations between two women veterans triggered a realization that our military service had been 'deeply odd'. Jointly authored by a historian and a social scientist, both have served in different services, through different conflicts, for different lengths and left for different reasons. Nonetheless, they have been fascinated by the parallels in their experiences of transition from military service to the academic researcher. This paper considers how their gendered military identity was constructed and negotiated such that they could not see their gendered experiences as 'deeply odd' when serving and can only see this now because their studies have challenged them to reflect critically. Women veterans are largely invisible in academia in contrast to the prominence of male veterans, particularly in military history and mainstream defence studies. Yet, the field of Critical Military Studies places women veteran researchers in a unique position of insider-outsider; still stained by our past compliance with the military institution – still outsiders – yet endeavouring now to find a new home as an 'insider', as critical feminist researchers. They find their identity as critical feminist scholars distances themselves from the military they want to remain engaged with and yet they are also viewed as 'deeply odd' themselves in the eyes of the critical feminist scholar community. Drawing on their personal experience, this paper argues that using the concept of the 'deeply odd' helps explore the dynamics of women veterans as critical feminist scholars with their insider-outsider status.